(3TQM UOQ GdebGdI GdYGTQI ef cJGH GbdjOS aj CUhd GdebGOjQs - (3YeQ Hf Ydj Hf ZjdGf GdHdNj, GaVd GdOjfs ((3fhM Hf jhSa Hf Ydi s)
(3ChdgG (B:s
(3bGd YeQ Hf Ydi Hf ZjdGf hde jcf ef TQMg GdG Gf LYd ddebGOjQ CeKdI YOOjI s
(3BNQgG (B:s
(3hdgPG GdeYfi GdJeS efj aUdG GdhbJ hGddg CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(599) s
Keywords: (3GdQjGVjGJs